MENINGKATKAN PRESTASI BELAJAR AQIDAH AKHLAK MELALUI KETERAMPILAN MENGELOLA KELAS PADA SISWA KELAS IV MI - Mukarromah, Aenullael; Bayu Aditama, Wiranda; Hafizin; Fibrianto, Sutrisno (JURNAL KAJIAN ISLAM MODERN, 2024)
The aim of this research is to improve learning achievement in Aqidah Akhlak learning through class management skills in class IV students at Madrasah Ibtidiyah. The type of research used is Classroom Action Research which is carried out in 2 cycles consisting of 2 meetings with 4 stages in each cycle, namely planning, implementing actions, observing and reflecting. As subjects in the research were teachers of the Aqidah Akhlak subject and class IV Madrasah Ibtidaiyah students, totaling 25 students. The data collection methods used are observation, tests, documentation and interviews. Observations include teacher teaching activities in managing the class and students' actions during implementation in each cycle. The test used is a multiple choice question test to determine the increase in student learning outcomes which is carried out in the performance of each cycle. Interviews were conducted with teachers and students. The data in this research includes two types, namely quantitative and qualitative data. The results of the research can be concluded that the application of classroom management skills can improve Aqidah Akhlak class IV learning achievement at Madrasah Ibtidaiyah. This is shown from the pre-cycle student scores below 70 with an average class score of 62.4 or only 10 students who completed. and classical completeness is 40% out of 25 people. In cycle I, it was found that teacher activity was quite active, with an average student activity score of 10.4 in the quite active category. From the evaluation results data from cycle I, it was found that 72% of students or 18 students completed classical completion. Meanwhile, in cycle II, teacher activity was classified as very active, namely with an average student activity score of 22.2 in the very active category, and from the results In the second cycle evaluation, 92% of students or 23 students completed classical completion. The increase in student learning outcomes in the Aqidah Akhlak subject increased by 52% from pre-cycle to cycle II.